A history of Codex Bezae’s text in the Gospel of Mark - Lorenz, Peter (Arbeiten Zur Neutestamentlichen Textforschung Series, 2021)
Since 1963 the Institute for New Testament Textual Research (Münster) has been publishing pivotal research and studies on textual criticism and textual history of the Greek New Testament in its series Arbeiten zur Neutestamentlichen Textforschung (ANTF). The series provides a research and discussion forum and supplies editions and instruments for researching and evaluating the New Testament in its primary transmission and the early translations.